Jurnal Penyuluhan: Tingkat Kompetensi Petani Agribisnis Sayuran Pada Lahan Sempit di Kota Banda Aceh dan Kabupaten Aceh Besar - Muhibuddin , Siti Amanah, Dwi Sadono (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The research objectives are to analyze the level of agribusiness competencies of smallholders with vegetable planting, the correlated factors with agribusiness competence of smallholders with vegetable planting, and the strategies of increasing agribusiness competence of smallholders with vegetable planting.